Brief mindfulness breathing exercises and working memory capacity: Findings from two experimental approaches - QUEK, Frosch Y. X. (Institutional Knowledge at Singapore Management University, 2021)
Mindfulness training has been extensively researched and found to elicit positive effects on cognitive performance, including working memory capacity. Benefits to cognitive function have been extended to brief mindfulness training as well. However, not much is known about its effect on working memory capacity. The current study examined the effects of a single 15-min session of mindful attention to breathing compared to a 15-min session of mind-wandering exercise in a within-subjects experimental design (Study 1; N = 82) and a between-subjects experimental design (Study 2; N = 424). Contrary to our hypotheses, in both experiments, we did not find any evidence that participants in the mindfulness condition outperform the control condition on an operation span task (Study 1) and a symmetry span task (Study 2). These results suggest that a single session of mindful practice may not be sufficient to enhance working memory capacity.